Reactivity and selectivity in the polymerization of multifunctional acrylic monomers by chiral zirconocenium catalysts - Peña, Fernando Vidal, author; Chen, Eugene Y.-X., advisor; Finke, Richard G., committee member; Strauss, Steven, committee member; Fisher, Ellen, committee member; Wang, David, committee member (Colorado State University. Libraries, 2017)
Described in this dissertation are the results of investigating the reactivity and selectivity in the polymerization of multifunctional acrylic monomers by chiral cationic zirconocenium catalysts. The unprecedented precision polymer synthesis method developed in this work-the polymerization of polar divinyl monomers that is not only living but also simultaneously chemoselective and stereoselective-has enabled the synthesis of well-defined highly stereoregular functionalized polymers bearing reactive C=C bonds on every chiral repeat unit. Thus, under ambient conditions, chiral ansa-ziroconocenium catalysts of the appropriate symmetry (C2- vs CS-ligated) have afforded highly isotactic and highly syndiotactic double-bond-carrying polymers, respectively, with controlled molecular weights and narrow dispersities. The enantiomorphic-site controlled, conjugate-addition coordination polymerization mechanism is responsible for the observed high degree of control over the polymerization characteristics, chemoselectivity and stereochemistry. Soft-material applications of such stereoregular and reactive ene-bearing polymers have also explored, including chemical post-functionalization to functional materials, photocuring to elastic films, and molecular recognition to robust crystalline supramolecular stereocomplexes and helical C60 inclusion complexes. A class of important biorenewable monomers containing one methacrylic C=C and two ester groups, namely itaconic esters and anhydride, have been examined, for the first time, for their polymerizability towards both neutral and cationic bridged ansa-zirconocenes and nonbridged zirconocenes. This investigation has yielded a fundamental understanding of the reactivity of the zirconocene complexes towards such monomers, specifically the fundamental chain initiation and propagation steps, structures of resting metallocyclic chelates, as well as kinetic and thermodynamic intermediates.
Keywords: chemoselectivity; polymerization; stereoselectivity; methacrylate; catalysts; post-functionalization